Trans Umbilical Lap Assisted Appendectomy (Two Port Technique) A Modern Approach Of Treatment Of Appendicitis - Shawkat Mohamad, Abdelhalem; Ali Ibrahim, Ibrahim; Ahmed Mohamed Nagaty, Mohamed; Yassen Fathy, Khalaf; Magdy Abdelmohsen, Sarah; M Akoula, Ahmed (Journal of Neonatal Surgery, 2025)
Background: Incisions used for open appendectomy vary widely, but the most common is proposed by McBurney. The cosmetic result is poor when the incisions are oblique, horizontal, or vertical. TULAA is considered a minimally invasive technique combining simplicity, short operative time, low costs, and low rate of complications Aim: to assess the practicality of two-port laparoscopic appendicectomy (TPA) treatment of appendicitis Patients and methods: This descriptive cross-sectional study was performed on 100 patients less than 15 years with a diagnosis of acute appendicitis. Following an approval from the ethics committee, patients were subjected to two-port laparoscopic appendicectomy over a 6-month period. Results: The mean operative time was approximately 57.9 minutes with an 11% conversion rate to open surgery. Hospital stays averaged 3.6 days and 9% of patients developed intra-abdominal abscesses. A higher body mass index was identified as a significant predictor of complications. Conclusion: Two-port TULAA is a feasible, safe, and cosmetically advantageous alternative to conventional appendectomy methods. Further multicenter studies with extended follow-up are recommended to confirm these promising outcomes. Larger trials needed.